Households Food Security and Perception of Food Nutrition in Enugu State, Nigeria - Stella Nwawulu Chiemela; Chinedum Jachinma Chiemela; Christian Chikamso Apeh; Maryqueen Chikaosolu Ileka (Journal of Agricultural Extension, 2022)
There is no empirical literature available on the food security status of Enugu State, Nigeria and the need to provide policymakers and educationists with the much-needed information for effective projects and interventions for householdâ€™s welfare in the State cannot be overemphasized. The study used household data from 240 randomly selected respondents to assess the food and nutrition security of households in Enugu State. Households Food Insecurity Access Scale (HFIAS) and Household Dietary Diversity Score (HDDS) were used to describe the householdsâ€™ food security levels. Descriptive statistics were also used to describe the householdsâ€™ socioeconomic characteristics, food sources, factors that affect their food choices and knowledge of food nutrition and balanced diet. From the result, only thirty percent of the respondents were food secured, the remaining seventy percent had some level of food insecurity. The mean score of the dietary diversity of households was 5.95 out of 12. The respondents showed to have little or no knowledge of food nutrition and balanced diet. The study recommends that educational programmes on food and nutrition security should be conducted and encouraged by extension agents, governments and non-governmental agencies to enlighten households. A follow-up survey is also recommended to provide up-to-date information on food security trends and statistically test the determinants of food security levels of households in the State.